2016
DOI: 10.1089/pop.2015.0129
|View full text |Cite
|
Sign up to set email alerts
|

Population Health: Curriculum Framework for an Emerging Discipline

Abstract: "Population health" has come to describe an array of initiatives supporting new care and reimbursement models that reward health outcomes rather than volume of services. However, without a standard definition of population health and a comprehensive inventory of the core competencies and knowledge its practitioners must possess, ongoing efforts to address community health outcomes will be hampered. A literature search of peer-reviewed and gray literature, a curriculum scan of current graduate health programs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Also, major governmental and independent stakeholders in the field of population health provide reports and white papers that in essence define the field for their target audiences. 32 The research team identified those articles and reports containing knowledge domains and topics that were deemed appropriate for inclusion in a population health framework as well as those that introduced specific population health measures.…”
Section: Methodsmentioning
confidence: 99%
“…Also, major governmental and independent stakeholders in the field of population health provide reports and white papers that in essence define the field for their target audiences. 32 The research team identified those articles and reports containing knowledge domains and topics that were deemed appropriate for inclusion in a population health framework as well as those that introduced specific population health measures.…”
Section: Methodsmentioning
confidence: 99%
“…In the impactful shift from "volume to value," the health care industry must address the need for health equity (Kindig and Milstein 2018), whether through investing in external consultants, creating new positions, or professional development. The PHM skill set thus includes an understanding of health outcomes, health systems, payment models, quality, business intelligence, communication, analytics, and social factors (Harris, Puskarz, and Golab 2016).…”
Section: Example Curriculum Of An Ispmentioning
confidence: 99%
“…The underlying assumptions behind the population health concept used by the authors have evolved from previous works in the 1990s, namely in Canada, putting the focus on the nonmedical determinants of health to understand why some populations are healthier than others and on their role to take action on population health improvement and reduction of health inequalities [1315]. This perspective, described as a population health approach, is understood as an emerging discipline and as a concept extending public health model [16] by considering a wide range of health indicators and dimensions which are not part of traditional public health practice, such as education, income, and employment along with components of physical and built environments (e.g., urban design, housing, air quality) [12, 17]. …”
Section: Introductionmentioning
confidence: 99%